Expressive Speech Acts in User Comments on the BBC Learning Podcast “Better Speaking” - Anindita Dewangga Puri (Universitas Islam Negeri (UIN) Sultanah Nahrasiyah Lhokseumawe, 2026)
Nowadays, there are a lot of digital platforms that offer interactive spaces for people to interact with each other. These platforms allow people to share information, exchange thoughts and opinions, give feedback, ask questions, or discuss a particular topic. YouTube is one of the most popular platforms that provides a space for people to give comments or responses to their posts. This natural interaction can be examined from a pragmatic perspective, especially in relation to how they express their emotional response in a written form. This research focuses on identifying and analyzing expressive speech acts in the user comments on the “Better Speaking” podcast by BBC Learning English, a globally recognized English learning channel. The research uses a descriptive qualitative method to examine 212 selected user comments from eight podcast episodes. The expressive speech acts were categorized into thanking, praising, complimenting, complaining, and lamenting. The findings show that thanking and praising are the most frequent types of expressive speech acts that indicate the existence of a dominant positive interaction pattern. Moreover, the comments also reveal four main pragmatic functions: affective alignment, relational work, feedback evaluation, and identity projection. These results suggest that user comments not only express their emotion but also contribute to a supportive and meaningful digital learning environment.